The healthfulness and prominence of sugar in child-targeted breakfast cereals in Canada - Potvin Kent, Monique; Cameron, Cher; Philippe, Sarah (Université d'Ottawa | University of Ottawa, 2017)
Introduction: The objective of this study was to compare the nutritional content and healthfulness of child-targeted and “not child-targeted” breakfast cereals and to assess the predominance of added sugar in these products. Methods: We collected data on the nutritional content of 262 unique breakfast cereals found in the five largest grocery store chains in Ottawa (Ontario) and Gatineau (Quebec). We noted the first five ingredients and the number of added sugars present in each cereal from the ingredients list. The various cereal brands were then classified as either “healthier” or “less healthy” using the UK Nutrient Profile Model. We assessed each cereal to determine if it was child-targeted or not, based on set criteria. Statistical comparisons were made between child and not child-targeted cereals. Results: 19.8% of all breakfast cereals were child-targeted, and these were significantly lower in total and saturated fat. Child-targeted cereals were significantly higher in sodium and sugar and lower in fibre and protein, and were three times more likely to be classified as “less healthy” compared to not child-targeted cereals. No child-targeted cereals were sugar-free, and sugar was the second most common ingredient in 75% of cereals. Six breakfast cereal companies had child-targeted product lines that consisted entirely of “less healthy” cereals. Conclusion: There is a need for regulations that restrict food marketing to children and youth under the age of 17 on packaging to reduce their appeal to this age group. Children’s breakfast cereals also need to be reformulated through government-set targets, or through regulation should compliance be deemed unacceptable.
Keywords: breakfast; cereal; children; food supply; marketing; nutrition; obesity; sugar